KELAYAKAN BUKU CERITA ANAK KARYA MAHASISWA PGSD UNESA UNTUK PEMBELAJARAN APRESIASI SASTRA - Maryam Isnaini Damayanti; Wahyu Sukartiningsih; Hendratno Hendratno; Heru Subrata; Susetyo Rukmi; Nurul Istiq’faroh (Institut Pendidikan Tapanuli Selatan, 2023)
Being able to write a child's story is one of the competencies that must be mastered by prospective elementary school teachers. Through the story written, a teacher can also form the character of his students without being patronizing. Children's stories function to smooth the taste in students, enrich the mind, and equip with other forms of skills. In addition, it also fills the inner wealth of students with the moral values of life. For that, children's story work written by students needs to be analyzed for eligibility. Through this study, analyzed the feasibility of 36 children's stories in a book entitled